Synthesis of Isosteviol analogues as potential protective agents against Doxorubicin-induced cardiomyopathy in zebrafish embryos. Issue 14 (15th July 2019) - Jayachandra, R.; Zhao, Haishan; Cheng, Zuchun; Luo, Liping; Sun, Tingwei; Tan, Wen
Graphical abstract: Abstract: Doxorubicin (DOX) is a powerful anthracycline antibiotic agent which is widely used to treat various types of cancers. Despite efficacy, it displays severe cardiotoxic side effects. Discovery of novel and effective protective agents against DOX-induced cardiotoxicity has been a subject of great interest. Herein, we report the synthesis of two series of analogues of Isosteviol (ISV) 1 with modifications at C-16, C-19 positions as the first series and at C-15, C-16 positions as the other series. Interestingly second series analogues have shown a potential protective effect against DOX-induced cardiotoxicity in zebrafish embryos in vivo . Further, we have demonstrated that the synthesized new analogues of ISV, prevented the morphological distortions caused due to DOX cardiotoxicity in zebrafish heart and the associated cardiac impairments.